GENERAL CHARACTERISTICS OF THE LEXICAL AND STYLISTIC TRANSLATION MATCHES THE KAZAKH LANGUAGE OF THE BOOK “HISTORY OF THE KAZAKH CULTURE” SU BAIHAY (Journal of Oriental Studies, 2019)
The article analyzes and compares the methods of translation of realities in the book Su-Beihay “History of Kazakh Culture” from Chinese into Kazakh. And also in the article problems and methods of translation, the problem of finding translation correspondences, namely lexical and stylistic correspon- dences, difficulties in translating an artistic text into unrelated languages are considered.Key words: translation, text, compliance, context, transliteration ,term.